BLOOD GLUCOSE AND CHOLESTEROL LEVELS OF BALI CATTLE THAT EXPERIENCED REPEATED BREEDING, IN THE VILLAGE OF SOBANGAN, MENGWI DISTRICT, BADUNG REGENCY, BALI - Khairunnisa Zahra Ravenska; Desak Nyoman Dewi Indira Laksmi; Anak Agung Sagung Kendran (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Previously, there have been many cases of suboptimal reproductive function in Bali cattle leading to repeated breeding. Blood biochemical profiles, such as blood glucose and cholesterol, can be parameters that describe body health, including the reproductive system. This study aims to determine the levels of blood glucose and cholesterol in Bali cattle that experience repeated mating. This study used an observational study with a completely randomized design (CRD) consisting of fertile and repeated mating Bali cattle groups. Sample determination was carried out based on criteria using a questionnaire, after which sampling was carried out, then an examination was carried out in the laboratory using the Glucose Oxidase-Phenol Amino Phenazone (GOD-PAP) and Cholesterol Oxidase-Peroxidase Aminoantypirin (CHOD-PAP) methods. The results showed that the average blood glucose levels in fertile and repeated mating Bali cattle were 85.55 mg/dL and 99.97 mg/dL, respectively. The average blood cholesterol levels of fertile and repeated mating Bali cattle were 131.84 mg/dL and 149.56 mg/dL, respectively. There was no significant difference between the fertile and repeated mating groups. It was concluded that the average blood glucose and cholesterol levels between fertile and repeated mating Bali cattle in this study did not affect the occurrence of repeated mating. Further research is needed on a larger scale.